Soil physical and chemical quality on no tillage cultivated with vegetables – A review (Research, Society and Development, 2022)
The objective of this review is to provide a holistic view on the chemical and physical quality of soils in no-tillage systems, to understand the main benefits that practices cause to soils. It is important to mention that the conservation practices (crop rotation and succession, for example) have been expanding every year, showing that it can be an easily adopted practice and that it can be integrated into different cultures and can be replicated at a commercial level, thus contributing to the adoption of the no-tillage system. The C:N ratio of the crop chosen for rotation/succession is responsible for the nutrient release and straw degradation rates. Thus, plant diversity is what guarantees the best crop rotation/succession ratio, bringing physical and chemical benefits to the soil for high crop productivity. The soil cover produced by these plants guarantees the consolidation of no-till, protecting the soil from erosion caused by the surface runoff of rainwater, during the harvest and off-season. It is expected that the adoption of the no-till cropping system will result in significant improvements in soil quality, contributing to the social, environmental and financial development of rural properties, making the system highly accepted by food producers.